Fungal communities are passengers in community development of dune ecosystems, while bacteria are not - Gao, Chenguang; Bezemer, T Martijn; van Bodegom, Peter M; Baldrian, Petr; Kohout, Petr; Mancinelli, Riccardo; van der Hagen, Harrie; Soudzilovskaia, Nadejda A (Ecology, 2024)
An increasing number of studies of above-belowground interactions provide a fundamental basis for our understanding of the coexistence between plant and soil communities. However, we lack empirical evidence to understand the directionality of drivers of plant and soil communities under natural conditions: 'Are soil microorganisms driving plant community functioning or do they adapt to the plant community?' In a field experiment in an early successional dune ecosystem, we manipulated soil communities by adding living (i.e., natural microbial communities) and sterile soil inocula, originating from natural ecosystems, and examined the annual responses of soil and plant communities. The experimental manipulations had a persistent effect on the soil microbial community with divergent impacts for living and sterile soil inocula. The plant community was also affected by soil inoculation, but there was no difference between the impacts of living and sterile inocula. We also observed an increasing convergence of plant and soil microbial composition over time. Our results show that alterations in soil abiotic and biotic conditions have long-term effects on the composition of both plant and soil microbial communities. Importantly, our study provides direct evidence that soil microorganisms are not "drivers" of plant community dynamics. We found that soil fungi and bacteria manifest different community assemblies in response to treatments. Soil fungi act as "passengers," that is, soil microorganisms reflect plant community dynamics but do not alter it, whereas soil bacteria are neither "drivers" nor "passengers" of plant community dynamics in early successional ecosystems. These results are critical for understanding the community assembly of plant and soil microbial communities under natural conditions and are directly relevant for ecosystem management and restoration.
Keywords: houby; rostliny; Soil Microbiology; bacteria; whole‐soil inoculation; ekosystém; fungi; Bacteria; coexistence; soil microbial community; field experiment; Fungi; Plants; ecosystem restoration; půdní mikrobiologie; plant community; sterilization; Ecosystem; ecosystem dynamics